TASKS AND PRINCIPLES OF INTERACTION OF THE MINISTRY OF DEFENSE OF UKRAINE WITH OTHER STATE BODIES - Ponomarova, D. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The article substantiates the relevance of clarification, formulation and delimitation of tasks and principles of interaction of the Ministry of Defense of Ukraine with other state bodies. It is noted that one of the essential signs of interaction is the commonality of the tasks performed, objectively substantiates the expediency of combining the efforts of two or more participants in the interaction. The Ministry of Defense of Ukraine interacts with other state bodies, primarily with those that are part of the security and defense sector, to ensure the formation and implementation of state policy on national security in the military sphere, defense and military development in peacetime and a special period. The weight of these tasks and their strategic importance for the state, society and every citizen determines the importance of establishing effective interaction, depends primarily on the basic principles of its organization and implementation. Therefore, the article substantiates the relevance of the study of the tasks and principles of interaction of the Ministry of Defense of Ukraine with other state bodies. The article analyzes the provisions of the current administrative legislation regulating the task of the Ministry of Defense of Ukraine with other state bodies. The tasks of interaction of the Ministry of Defense of Ukraine with other state bodies in the context of two interrelated and complementary groups have been clarified, formulated and delimited: 1) the tasks set for the Ministry of Defense of Ukraine are planned to be achieved, including through interaction with other state bodies; 2) tasks of direct interaction of the Ministry of Defense of Ukraine with other state bodies, the expected results from the implementation of which determine the actual expediency of this interaction. The highlighted principles of interaction of the Ministry of Defense of Ukraine with other state bodies, which were divided into two complementary groups: 1) basic principles of the Ministry of Defense of Ukraine, including its interaction with other state bodies: a) universal management principles; b) regulatory and legal principles; c) special principles of activity of the Ministry of Defense of Ukraine; 2) specific principles of interaction of the Ministry of Defense of Ukraine with other state bodies, on which this interaction is directly based and on which the effectiveness of its implementation depends.
Keywords: administrative and legal support, interaction, interaction efficiency, interaction tasks, Ministry of Defense of Ukraine, principles of interaction